Genomic monitoring unveil the early detection of the SARS‐CoV‐2 B.1.351 (beta) variant (20H/501Y.V2) in Brazil. Issue 12 (19th July 2021) - Slavov, Svetoslav N.; Patané, José S. L.; Bezerra, Rafael dos Santos; Giovanetti, Marta; Fonseca, Vagner; Martins, Antonio J.; Viala, Vincent L.; Rodrigues, Evandra S.; Santos, Elaine V.; Barros, Claudia R. S.; Marqueze, Elaine C.; Santos, Bibiana; et al.
Abstract: Sao Paulo State, currently experiences a second COVID‐19 wave overwhelming the healthcare system. Due to the paucity of SARS‐CoV‐2 complete genome sequencing, we established a Network for Pandemic Alert of Emerging SARS‐CoV‐2 Variants to rapidly understand and monitor the spread of SARS‐CoV‐2 variants into the state. Through analysis of 210 SARS‐CoV‐2 complete genomes obtained from the largest regional health departments we identified cocirculation of multiple SARS‐CoV‐2 lineages such as B.1.1 (0.5%), B.1.1.28 (23.2%), B.1.1.7 (alpha variant, 6.2%), B.1.566 (1.4%), B.1.544 (0.5%), C.37 (0.5%) P.1 (gamma variant, 66.2%), and P.2 (zeta variant, 1.0%). Our analysis allowed also the detection, for the first time in Brazil, the South African B.1.351 (beta) variant of concern, B.1.351 (501Y.V2) (0.5%), characterized by the following mutations: ORF1ab: T265I, R724K, S1612L, K1655N, K3353R, SGF 3675_F3677del, P4715L, E5585D; spike: D80A, D215G, L242_L244del, A262D, K417N, E484K, N501Y, D614G, A701V, C1247F; ORF3a: Q57H, S171L, E: P71L; ORF7b: Y10F, N: T205I; ORF14: L52F. The most recent common ancestor of the identified strain was inferred to be mid‐October to late December 2020. Our analysis demonstrated the P.1 lineage predominance and allowed the early detection of the South African strain for the first time in Brazil. We highlight the importance of SARS‐CoV‐2 active monitoring to ensure the rapid detection of potential variants for pandemic control and vaccination strategies. Highlights Identification of B.1.351 (beta) variant of concern in the Sao Paulo State. Dissemination of SARS‐CoV‐2 variants of concern and interest in the Sao Paulo State. Mutational Profile of the circulating variants of concern and interest.